Common bean cultivar BRS Ametista with large Carioca grains and disease resistance - Melo,Leonardo Cunha (2012)
BRS Ametista is a common bean cultivar with Carioca grain and yields similar to cultivar Pérola, but with larger grain size, resistance to anthracnose and Fusarium wilt. It is recommended for 18 states in all regions of Brazil and can be planted on over 95% of the area used for common bean in the country.